Methodology of botulinum therapy in the treatment of dystonic scoliosis in generalized dystonia (clinical case) - V. K. Misikov; A. P. Kovalenko; A. A. Kondur (Нервно-мышечные болезни, 2023)
Dystonic scoliosis as one of the forms of generalized dystonia is a highly disabling form of dystonia, which can lead to damage to internal organs (lungs, heart) and the peripheral nervous system, including the spinal cord. Almost always, those muscles that are involved in the formation of a dystonic posture in generalized dystonia have not been studied in terms of the effectiveness of treatment with botulinum toxin type A and are not reflected in the instructions. As a result, there is no understanding of the general motor interaction with differentiation into targeted and non-targeted muscles, administration doses and control methods.The aim of the work was to evaluate the efficacy and tolerability of high doses of botulinum toxin type A in dystonic scoliosis, as well as to present the introduction of botulinum toxin type A using ultrasound and electromyographic control. We have described a clinical case of a 19-year-old patient suffering from generalized dystonia with S-shaped dystonic scoliosis of the III degree. Deep brain stimulation was recommended as a treatment for the patient. During the waiting period for the timing of the operation, we attempted symptomatic therapy using the drug incobotulotoxin A. Over the next year and a half, 700 units of botulinum toxin type A were administered under ultrasound and electromyographic control every 3–4 months. As a result, treatment of trunk dystonia in the patient during the observation period led to a clinically significant decrease in the degree of curvature (from 37° to 27°, from III to II degree of scoliosis) in the absence of undesirable effects of the drug, including generalized muscle weakness. According to the repeated conclusion of the council of neurosurgeons, surgical intervention is not indicated for the patient due to the positive effect of the introduction of botulinum toxin type A.